373. Comparison of the Epidemiology and Pathogens Cultured from Patients Hospitalized with SARS-CoV-2 Positive versus SARS-CoV-2 Negative in the US: A Multicenter Evaluation. (31st December 2020) - Puzniak, Laura A; Finelli, Lyn; Bauer, Karri A; Moise, Pamela; Yu, Kalvin; De Anda, Carisa; Vankeepuram, Latha; Parikh, Prashant; Gupta, Vikas
Abstract: Background: Past experiences with viral epidemics have indicated an increased risk for bacterial, fungal, or other viral secondary or co-infections due to patient characteristics, healthcare exposures and biological factors. It is important to understand the epidemiology of these infections to properly treat and manage these complex patients. This study evaluates the frequency, source, and pathogens identified among SARS-CoV-2 tested patients. Methods: This was a multi-center, retrospective cohort analysis of SARS-COV-2 tested patients from 271 US acute care facilities with >1 day inpatient admission with a discharge or death between 3/1/20–5/31/20 (BD Insights Research Database [Becton, Dickinson & Company, Franklin Lakes, NJ]). We evaluated pathogens identified from blood, respiratory tract (upper/lower), urine, intra-abdominal (IA), skin/wound and other sources and classified them with respect to Gram-negative (GN), and Gram-positive (GP) bacteria, fungi, and viruses among those SARS-CoV-2 positive and negative. Results: There were 599, 709 admissions with 142, 054 (23.7%) patients tested. Among those SARS-CoV-2 tested, 17, 075 (12%) were positive and 124, 979 (78%) were negative. The most common specimen collection sites (Table 1) and pathogens (Table 2) are shown. Higher rates of urine and respiratory cultures and higher rates of P. aeruginosa and fungi were seen in SARS CoV-2 positive patients. The top pathogens for urine cultures were Escherichia coli and Klebsiella pneumoniae, for blood Staphylococcus aureus and Escherichia coli and respiratory Staphylococcus aureus and Pseudomonas aeruginosa. SARS-CoV-2 positive patients had an overall longer length of stay (LOS) than negative, which almost doubled when a positive pathogen was identified. Conclusion: There were similar rates of positive pathogen identification among SARS-CoV-2 test positive and negative patients, which might highlight similarities in clinical presentation. However, SARS-CoV-2 positive patients had longer hospital LOS and LOS increased with positive culture. Sources of infection and pathogens varied based on a positive or negative SARS-CoV-2 result. Identifying likely causative pathogens of co-infections in the era of SARS-CoV-2 is critical for treatment optimization. Disclosures: Laura A. Puzniak, PhD, Merck (Employee) Lyn Finelli, DrPH, MS, Merck & Co Inc, (Employee) Karri A. Bauer, PharmD, Merck Research Laboratories (Employee) Pamela Moise, PharmD, Merck & Co., Inc. (Employee, Shareholder) Kalvin Yu, MD, Becton, Dickinson and Company (Employee)GlaxoSmithKline plc. (Other Financial or Material Support, Funding) Carisa De Anda, PharmD, Merck & Co Inc, (Employee) Latha Vankeepuram, MS, BD (Employee) Prashant Parikh, n/a, Becton, Dickinson and Company (Employee) Vikas Gupta, PharmD, BCPS, Becton, Dickinson and Company (Employee, Shareholder)GlaxoSmithKline plc. (Other Financial or Material Support, Funding)